The Influence of Population Behavior and Settlement Environment on the Incidence of Filariasis in Sigi Regency, Central Sulawesi, Indonesia - Santriana, Santriana; Ramadona, Aditya Lia; Gunawan, Gunawan (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: A health issue is filariasis including in Sigi Regency, brought on by filarial worms and spread by mosquito bites. Filariasis is a parasitic infection that threatens about one-third or 1.3 billion of the world's population in 83 countries that are vulnerable to filariasis. This research intends to examine the impact of behaviour and environment on the occurrence of filariasis in the Sigi Regency. Methods: The study used an observational analytic method with a case control approach, involving 114 people from 13 villages in Sigi Regency, of whom 38 were cases and 76 were controls. The control group is people who live in the same environment as the case group. The data collection methods were a survey and an environmental assessment. Results and Discussions: The logistic regression analysis revealed that the most influential factors for the occurrence of filariasis in endemic regions in Sigi Regency were mosquito breeding sites with Odds Rasio (OR) value =8.57 (2.43-34.33), p-value = <0.001, existence of animal pens with OR value=5.16 (1.15-29.44), p-value = 0.044, and not using anti-mosquito medication with OR value = 6.06 (1.54-27.56), p-value = 0.013. Conclusion: The breeding habitats of disease-transmitting mosquitoes, the presence of animal pens and the habit of not using anti-mosquito medication are the dominant risk factors related to the occurrence of filariasis in endemic regions in the Sigi Regency.